Hubungan Antara Tingkat Self-Regulation Remaja dan Kesiapan Kewirausahaan di Masa Dewasa: Studi Kasus di Sumatera Utara - Rajagukguk, Frederick Rudy Sentosa; Harahap, Hastuti Handayani; Arifin, Indra Welly (Management And Business Progress, 2025)
This study aims to analyze the relationship between adolescents’ level of self-regulation and entrepreneurial readiness in adulthood. Self-regulation refers to an individual’s ability to control thoughts, emotions, and behaviors to achieve long-term goals, while entrepreneurial readiness describes the extent to which individuals possess motivation, knowledge, and skills to start and manage a business. The research employed a qualitative approach using a case study of adolescents in North Sumatra Province. Data were collected through in-depth interviews, observations, and documentation, and analyzed thematically. The findings reveal a strong relationship between self-regulation ability and entrepreneurial readiness. Adolescents with higher levels of discipline, persistence, and emotional control demonstrated greater preparedness to engage in entrepreneurship. In addition to internal factors, family support, entrepreneurship education, and social environment also influence readiness levels. These results highlight the importance of strengthening self-regulation from adolescence as a foundation for developing resilient, independent, and innovative entrepreneurial character.